AB1272 TREATMENT OF RHEUMATOID ARTHRITIS WITH EXTENSION OF THE ANTI-TNF INTERDOSE INTERVALS. A MONOCENTRIC OFF-LABEL STUDY. (June 2019) - Kaltsonoudis, Evripidis; Pelechas, Eleftherios; V. Voulgari, Paraskevi; Drosos, Alexandros
Abstract : Background: Since the advent of anti-TNFs a revolution has been established in the treatment of Rheumatoid Arthritis (RA). Objectives: To evaluate the ability to safely extend the interdose intervals of the anti-TNFs in RA patients. Methods: Eighty-six patients with early RA fulfilling the ACR/EULAR classification criteria were included and followed-up at predefined times. All patients were on conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) plus an anti-TNF. At every visit, the disease activity score using the 28-joint count (DAS-28) as well as all the drug-related laboratory parameters were recorded. Clinical remission was defined as DAS-28 <2.6 for ≥12 months. RA patients in clinical remission had the possibility to extend interdose intervals. Results: A total number of 57 females and 29 males (mean age: 62.7±4.1 years; disease duration: 14.9±2.4 months) were included. 76 patients were in clinical remission, while 10 were in low disease activity. From those in clinical remission, 40 patients received adalimumab (ADA), 23 etanercept (ETN) and 13 golimumab (GOL). Regarding the extension of the interdose intervals, 29 patients were on ADA every 21 days, 11 every 30 days. Regarding the extension of the interdose intervals in patients receiving ETN: 15 patients were on ETN every 10 days, 8 every 15 days. Finally, 6 patients were on GOL at a dose interval of 35 days, 4 every 40 days, 3 every 45 days. Young, female and seronegative patients treated early with an anti-TNF had more chances of extending the interdose interval. Conclusion: We found that the extension of the interdose intervals of the anti-TNFs is a feasible option in early RA patients and it reflects not only significant clinical benefits for the patient but also economic benefits for the healthcare systems. Disclosure of Interests: None declared